Behavioral, Physiological and Hormonal Changes in Primiparous and Multiparous Goats and Their Kids During Peripartum - Paolo Cano-Suarez; Juan Pablo Damian; Rosalba Soto; Karen Ayala; Joob Zaragoza; Rocio Ibarra; Jesús Jonathan Ramírez-Espinosa; Laura Castillo; Irma Eugenia Candanosa Aranda; Angélica Terrazas (Ruminants, 2024)
The objective of this study was to evaluate the effect of maternal experience on behavior, progesterone and estradiol concentrations, weight and body condition in goats in the peripartum period, as well as the behavior and weight of the kids in the first hours after birth. Twenty multiparous and 10 primiparous dairy goats were enrolled. Behaviors such as walking, isolation, aggression, eating, inactivity and rumination were recorded in females during the last three days prior to the day of delivery, as well as the behaviors of the dam and her progeny in the first 2 h postpartum and the ability of the mother to discriminate between own kid and the alien one (selectivity test) at 2 h postpartum. Gestational and postpartum plasma progesterone and estradiol concentrations were determined. In the prepartum period there was a higher percentage of primiparous goats that were eating and remained less inactive compared to multiparous goats (p < 0.05). During the postpartum period, the lick latency to the kid was shorter in multiparous than in primiparous goats (p = 0.015). There was a greater proportion of kids born from multiparous (67%) than from primiparous (27%) that stood up in the first 30 min postpartum (p < 0.0001). Therefore, the proportion of multiparous kids (33%) than primiparous kids (9%) that were nursed within the first hour after birth was also higher (p < 0.0001). Progesterone and estradiol concentrations were not affected by maternal experience, neither in the prepartum nor the postpartum. In conclusion, maternal experience affected some behaviors at peripartum of the dam and vitality in the kid; however, the differences in behavior were not accompanied by differences in the variations in circulating estradiol and progesterone levels in the dam.